2005
DOI: 10.1111/j.1398-9995.2005.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of asthma care: results from a community pharmacy based survey

Abstract: Our results clearly identify a need to improve the management of asthma. Education programmes would be beneficial to improve asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
2
33
2
Order By: Relevance
“…One study conducted at 348 pharmacies in 9 French cities showed that patients with ARA have a low degree of control, as measured by a questionnaire, while the study volunteers reported that their asthma was well controlled or completely controlled. 23 Another study, conducted via patient questionnaire at 54 pharmacies in Flanders, showed a high percentage of insufficiently controlled asthmatic patients, as assessed by patient responses and peak expiratory flow rate. 21 A study carried out in Portugal evaluated the degree of asthma control with a self-reported diagnosis and concomitant asthma therapy using ACT.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study conducted at 348 pharmacies in 9 French cities showed that patients with ARA have a low degree of control, as measured by a questionnaire, while the study volunteers reported that their asthma was well controlled or completely controlled. 23 Another study, conducted via patient questionnaire at 54 pharmacies in Flanders, showed a high percentage of insufficiently controlled asthmatic patients, as assessed by patient responses and peak expiratory flow rate. 21 A study carried out in Portugal evaluated the degree of asthma control with a self-reported diagnosis and concomitant asthma therapy using ACT.…”
Section: Limitationsmentioning
confidence: 99%
“…The existing studies conducted in pharmacies mainly assess the control level of asthma and, in general, poor asthma control. [21][22][23] Identifying patients with poor ARA control may be the first step to helping patients obtain adequate treatment and to optimizing disease control.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…The design of the present study has been presented in a previous article [8]. A retrospective observational study was carried out in nine cities in France (Lyon, Montpellier, Caen, Nancy, Amiens, Dijon, Angers, Limoges, Besançon).…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…11 Laforest et al also observed similar results in a community pharmacy-based survey and reported that asthma control was satisfactory for only 28% of the patients during a fourweek period. 12 In this study, more than 50% of asthmatics reported that their asthma had an impact on work, school or home duties, considerably more than what was reported in AIRE where only 37.9% of adults reported that their asthma impaired their normal physical activities. 13 Nocturnal symptoms were common among the study patients; 66% reported having night symptoms in the last 4 weeks, which is more than what was reported in the AIRE study where only 36.2% of the adult asthmatic patients had disturbed sleep as a result of uncontrolled asthma symptoms.…”
Section: Discussionmentioning
confidence: 46%